ROS-responsive organosilica nanocarrier for the targeted delivery of metformin against cancer with the synergistic effect of hypoglycemia. Issue 30 (16th July 2021) - Yu, Yefei; Chen, Jifeng; Liu, Shuang; Cheng, Du
Abstract : A ROS-responsive organosilica nanocarrier for the targeted delivery of metformin against cancer with the synergistic effect of hypoglycemia is reported. Abstract : The controllable degradation of silica nanoparticles in anticancer therapy remains challenging. Here, we offer the first report that a thioketal (TK)-bond-containing bridged organoalkoxysilane has been synthesized. This allows for the fabrication of reactive oxygen species (ROS)-sensitive, degradable, bridged silsesquioxane nanoparticles (BS-NPs). These TK-bridged BS-NPs have a uniform size of 50 nm and are able to encapsulate a small molecule drug – metformin – using a reverse micro-emulsion method. After surface modification with a targeting peptide (RGD), these metformin-loaded BS-NPs exhibited a homologous tumor aggregation ability, leading to the efficient transport of metformin into the tumor cells. When combined with a clinically feasible fasting therapy, the RGD-decorated, metformin-loaded, ROS-responsive degradable BS-NPs remarkably increased the tumor sensitivity to metformin by 10 times compared with free metformin. The synergistic effects of metformin-loaded BS-NPs and fasting-induced hypoglycemia were verified through in vitro and in vivo experiments. This effect occurred by down-regulating the expression of pro-survival proteins pGSK3β and MCL-1. Collectively, these results demonstrate that the ROS-sensitive organosilica nanocarrier is a promising nanoplatform for drug delivery and provides an alternative approach for the combinatorial therapy of metformin and fasting therapy.